HUBUNGAN KEBIASAAN SARAPAN PAGI, KEBIASAAN JAJAN DAN KECUKUPAN CAIRAN DENGAN PRESTASI BELAJAR SISWA/SISWI DI SMKN 7 BEKASI - Fitriana Nurkhofifah (2022)
Learning is a very basic element in the teaching and learning process. In learning, it is absolutely necessary to concentrate on learning. At school age, many factors that affect learning achievement are breakfast habits, snack habits and learning motivation. The cause of the decline in learning achievement as a result of not having breakfast, the habit of eating out and the lack of water consumption so that intake becomes less and learning achievement decreases. Breakfast habits have a positive impact by providing optimal blood glucose levels for the learning process at school. Optimal blood glucose levels can support learning achievement and cognitive function. This study aims to determine the relationship between breakfast habits, snack habits and fluid adequacy with learning achievement in students at SMKN 7 Bekasi. This study uses a cross-sectional design with a sampling technique that is stratified random sampling. The selected sample was 62 students in grades 10 and 12. Data collection and collection was carried out using a questionnaire. The data obtained were tested using the Spearman test. The results of the analysis showed that breakfast habits (p = 0.001), snack habits (p = 0.000), and fluid adequacy (p = 0.001). This shows that there is a relationship between breakfast habits, snack habits and fluid adequacy with learning achievement in students at SMKN 7 Bekasi.